Analysis of the impacts of common components in multistage production system under uncertain conditions: Application of Taguchi method - Wazed, M.A.; Ahmed, S.; Nukman, Y. (Academic Journals, 2010)
The work desires to determine the optimum level of batch size in bottleneck facility, and to analyze the effect of common components on work-in-process (WIP) level and cycle time, in a multistage production system and uncertain environment created by machine breakdown and quality variation. Few simulation models were developed based on a live case from a company. The models were verified and validated with the historical data from the company and by face validity. Taguchi approach for orthogonal array was used in designing experiments and these were executed in WITNESS, a simulation package. It was observed that the variation in level of common component in the system had significant impact on the production WIP level and cycle time. The main contribution of this research is determination of the optimal level of batch size in a bottleneck resource under the uncertainties. This approach can be generalized to any multistage production system, regardless of the precedence relationships among the various production stages in the system.